2009
DOI: 10.1108/17538370910971018
|View full text |Cite
|
Sign up to set email alerts
|

Construction project procurement routes: an in‐depth critique

Abstract: PurposeThe purpose of this paper is to examine different categories of building project procurement routes based on organisational, contractual, financial and technical issues.Design/methodology/approachThe paper is based on review of literature and conditions of contracts. The UK construction industry serves as a general frame of reference. The Royal Institution of Chartered Surveyors survey of Contracts in Use from 1985 to 2004 is used to probe the share and value of contracts along different procurement rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 18 publications
1
39
0
2
Order By: Relevance
“…The research findings support the view of Beach et al (2005), Oyegoke et al (2009) and Wolstenholme (2009) in that professional development, education and training, operational and cultural change and commitment to continual improvement would be required if partnering, in austere times especially, is going to succeed in the future. Along with the recommendation of Morrell (2011) this could also bring cost savings to the industry in terms of buildability, standardisation, prefabrication and value engineering.…”
Section: Effects Of Austerity On Collaborative Procurementsupporting
confidence: 79%
“…The research findings support the view of Beach et al (2005), Oyegoke et al (2009) and Wolstenholme (2009) in that professional development, education and training, operational and cultural change and commitment to continual improvement would be required if partnering, in austere times especially, is going to succeed in the future. Along with the recommendation of Morrell (2011) this could also bring cost savings to the industry in terms of buildability, standardisation, prefabrication and value engineering.…”
Section: Effects Of Austerity On Collaborative Procurementsupporting
confidence: 79%
“…Por outro lado, as várias notícias sobre fraudes em licitações e execuções de obras públicas, tão recorrentes, podem ter levado ECQ1 a mencionar explicitamente que a ausência de uma gestão firme e eficaz por parte do órgão contratante pode dar lugar à ocorrência de ilícitos (vide tópico Lisura nos procedimentos/ comprometimento na Tabela 4). A necessidade de adequação das empresas à nova demanda levaria, na opinião dos entrevistados, à extinção, fusão, reestruturação e mesmo subcontratação entre as empresas do ramo, o que é ratificado por Puerto et al (2008), Park et al (2009), Oyegoke et al (2009 Chang et al (2010) citam a falta de experiência do projetista com construção e do construtor com projeto, abordando a questão da qualificação necessária a essas empresas. A afirmação de que as construtoras contratariam projetistas reside no fato de que na atualidade, pelo menos na amostra estudada, as empresas têm claramente expertises distintas, projeto ou construção, o que as levariam a princípio a subcontratações.…”
Section: Resultsunclassified
“…Contratualmente, o DB oferece um ponto singular de responsabilidade para os serviços de projeto e construção, o que é verdadeiro da perspectiva do contratante, mas não da empresa contratada, que pode subcontratar serviços para os quais não tenha expertise, ou integrar um consórcio de empresas (Chang, Shen & Ibbs, 2010;Park, Ji, Lee, & Kim, 2009;Puerto, Gransberg & Shane, 2008;Oyegoke, Dickinson, Khalfan, Mcdermott, & Rowlinson, 2009 Segundo outros autores, as principais vantagens do método DB de contratação estão no melhor desempenho em tempo (Hale et al, 2009;Konchar & Sanvido, 1998;Molenaar, Songer & Barash, 1999;Park et al, 2009;Yates, 1995), em custo (Konchar & Sanvido, 1998;Park et al, 2009;Yates, 1995), em qualidade (Park et al, 2009), em menos incidências de reivindicações, conflitos, disputas e ações legais (Molenaar et al, 1999;Park et al, 2009;Yates, 1995), menos trabalho administrativo, pedidos de esclarecimento, mudanças (Yates, 1995), maior construtibilidade 1 , mais inovação e melhor tomada de decisão (Molenaar et al, 1999;Yates, 1995).…”
Section: Ana Elisabete Cavalcanti De Albuquerque / Marcos André De Meunclassified
“…Similarly, procurement approaches and additional contract price provisions (e.g. lump sum, guaranteed maximum price, target cost, cost plus) are also commonly regarded as closely related (Oyegoke et al, 2009). Interestingly, a study by Tookey et al (2001) found that, in industrial practice, clients usually make amendments to mitigate risk and add usability to rigidly prescribed procurement systems that are imposed, in their view, by researchers and consultants when classifying procurement routes.…”
Section: The Construction Procurement Context Construction Procuremenmentioning
confidence: 99%